Thirty-day readmissions in children with complex chronic conditions - Daiana Basso; Carolina Bermúdez; Vanessa Carpio; Francisco Tonini; Fernando Ferrero; Mariano Esteban Ibarra (Elsevier, 2024)
Introduction: The rate of hospital readmission within 30 days of discharge is a quality indicator in health care. Paediatric patients with complex chronic conditions have high readmission rates. Failure in the transition between hospital and home care could explain this phenomenon. Objectives: To estimate the incidence rate of 30-day hospital readmission in paediatric patients with complex chronic conditions, estimate how many are potentially preventable and explore factors associated with readmission. Materials and method: Cohort study including hospitalised patients with complex chronic conditions aged 1 month to 18 years. Patients with cancer or with congenital heart disease requiring surgical correction were excluded. The outcomes assessed were 30-day readmission rate and potentially preventable readmissions. We analysed sociodemographic, geographic, clinical and transition to home care characteristics as factors potentially associated with readmission. Results: The study included 171 hospitalizations, and 28 patients were readmitted within 30 days (16.4%; 95% CI, 11.6%-22.7%). Of the 28 readmissions, 23 were potentially preventable (82.1%; 95% CI, 64.4%-92.1%). Respiratory disease was associated with a higher probability of readmission. There was no association between 30-day readmission and the characteristics of the transition to home care. Conclusions: The 30-day readmission rate in patients with complex chronic disease was 16.4%, and 82.1% of readmissions were potentially preventable. Respiratory disease was the only identified risk factor for 30-day readmission. Resumen: Introducción: La tasa de reingreso hospitalario a 30 días del alta es una medida de calidad de atención médica. Los pacientes pediátricos con patologías crónicas complejas tienen altas tasas de reingreso. La falla en la transición entre el cuidado hospitalario y domiciliario podría explicar este fenómeno. Objetivos: Estimar la tasa de incidencia de reingreso hospitalario a 30 días en pacientes pediátricos con patologías crónicas complejas, estimar cuántos son potencialmente prevenibles y explorar posibles factores asociados a reingreso. Materiales y método: Estudio de cohorte prospectivo incluyendo pacientes hospitalizados con patologías crónicas complejas de 1 mes a 18 años de edad. Se excluyeron pacientes con patología oncológica y cardiopatías congénitas. Se evaluaron el reingreso a 30 días y el reingreso potencialmente prevenible. Se valoraron características sociodemográficas, geográficas, clínicas y de la transición hacia el cuidado domiciliario. Resultados: Se incluyeron 171 hospitalizaciones; dentro de los 30 días reingresaron 28 pacientes (16,4 %; IC95% 11,6-22,7). De los 28 reingresos, 23, (82,1 %; IC95% 64,4-92,1) fueron potencialmente prevenibles. La patología respiratoria se asoció con mayor probabilidad de reingreso. No se encontró asociación entre reingreso a 30 días y los factores de la transición al cuidado domiciliario evaluados. Conclusiones: La tasa de reingreso a 30 días en pacientes con patología crónica compleja fue de 16,4 %, y el 82,1 % fueron potencialmente prevenibles. Únicamente la patología respiratoria se comportó como factor de riesgo para reingreso a 30 días.